Maintaining the sustainability of the regional credit guarantee institution in Indonesia / Ericke Fridatien, Grahita Chandrarin and Diana Zuhroh - Fridatien, Ericke; Chandrarin, Grahita; Zuhroh, Diana (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study aimed to analyze the effect of internal and macroeconomic factors on the financial performance of Regional Credit Guarantee Institutions (PT. Jamkrida) in Indonesia. Internal factors included: guarantee risk, gearing ratio, liquidity, and asset management, while macroeconomic includes: gross domestic product and inflation. The population was PT. Jamkrida in Indonesia, which were 18 in total, of which 16 met the requirements as the sample. The type of data was secondary data sourced from the PT. Jamkrida’s Annual Financial Report with observations for 2014-2020. The data analysis technique used was multiple regression analysis. This result: internal and external factors affected financial performance PT. Jamkrida in Indonesia. This result also proved the important role of the local government in maintaining PT. Jamkrida’s capital to ensure that bank loans to SMEs run well. This study contributes to the RBV theory by providing empirical evidence of the influence of internal resources and external conditions on PT. Jamkrida’s financial performance. But, this study has limitations as indicated by the results of an adjusted R square of 13.8%, so it is possible 86.2% of other variables can explain their effect on financial performance. Therefore, it offers opportunities to add other factor specifications, or other methods.